A companion to The origin and diffusion of shocks to regional interest rates in the United States, 1880 - 2002 - Hugh Rockoff; John S. Landon-Lane (Rutgers University, Department of Economics, 2006)
This paper contains all of the statistical results underlying our paper The Origin and Diffusion of Shocks to Regional Interest Rates in the United States, 1880-2002. It also contains a table of the underlying data, and a discussion of how the data was constructed.
Keywords: N22; 330; Interest rates; monetary unions